KAJIAN FONOLOGI BAHASA INDONESIA DALAM KUMPULAN VIDEO MAK BETI KARYA ARIF MUHAMMAD - Moh Syamsul Ma'arif; Siti Qorifatul Robayanah (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study was to describe the segmental elements in Mak Beti's video utterances and changes in sound / phonemes resulting from historical developments in Mak Beti's video utterances. The type used in this research is descriptive qualitative analysis. This research is a library research using data sources in the form of virtual audio and visuals of a vlogger by Arif Muhammad. The collection techniques used are observing and note-taking techniques, while the steps taken in collecting data are as follows (1) direct observation on the video Mak Beti, (2) understanding speech and recording data. The data analysis technique used is the data collection technique, data reduction, data presentation and conclusion drawing. The results of research and discussion in the video Mak Beti by Arif Muhammad are segmental elements and changes in sound / phonemes as a result of historical developments. The segmental elements in this discussion include vowels, consonants and semivowels. Meanwhile, changes in sound / phonemes as a result of historical developments discussed in Mak Beti's utterances include contraction including apheresis, syncope apocope. Diftongization, monophthongization and anaphthixis include epentesis, paragraph.